The impact and future of edible landscape on sustainable development of universities: a systematic literature review - Hang, Yu; Mohd Yunos, Mohd Yazid; Saidon, Mohd Nazri; Hussain, Mohd Amirul (Human Resource Management Academic Research Society, 2024)
Food security and sustainable development have always been the focus of interdisciplinary attention. This is not only a local issue, but also a global problem. Universities play an important role in promoting sustainable development of cities and communities, and face increasingly important challenges in balancing ecological sustainability. Therefore, this article provides a systematic review through PRISMA. Elaborate from three perspectives: ecological benefits, social benefits, and educational benefits. Research has shown that introducing edible landscapes can improve campus sustainability, educational content, and community engagement. The motivation for this study stems from the urgent need for food security and ecological sustainability. With the continuous growth of global population and the acceleration of urbanization, university campuses, as core areas of knowledge and innovation, can play a demonstrative role in sustainable development. The contribution of this study is to systematically analyze the multiple benefits of edible landscapes in university campuses, providing scientific basis for universities to create sustainable development environments. Introducing edible landscapes not only helps to improve the ecological diversity and environmental quality of campuses, but also enhances the awareness and participation of teachers and students in sustainable development, promotes community identity and social cohesion. Through this study, we hope to provide practical guidance for university administrators and policy makers to promote the practice of edible landscapes on a broader scale, thereby promoting the overall sustainable development of cities and communities.